Sustained ventricular tachycardia in a canine (Canis lupus familiaris) (Gaceta de Ciencias Veterinarias, 2015)
Ventricular tachycardia (VT) in dogs is a life-threatening cardiac arrhythmia, characterized electrocardiographically by three or more consecutive Premature Ventricular Complexes (PVC). PVCs in turn is presented as a wide and bizarre complex, with a longer duration than normal (more than 0.06 sec in dogs) that are not preceded by a P-wave .TV is considered sustained if it lasts more than 30 seconds. A clinical case of a male dog patient, 1 year old, breed Miniature Schnauzer, 9 kg, presented with syncope, lethargy, vomiting, tachycardia, and electrocardiographically diagnosed as sustained ventricular tachycardia and syncope of cardiac origin, is reported. It was show by X-ray and echocardiography had no morphological or structural damage to the heart. Intensive treatment with lidocaine bolus 2 mgs / kg every 10 minutes is established. After the third bolus patient evolves to sinus rhythm with ventricular premature complexes isolated. Maintenance treatment is administered with Atenolol, Enalapril and Furosemide, bed rest addition. Patient was monitored for 96 hours, evidencing that was stable. Subsequently, patient died suddenly after doing heavy exercise unauthorized.
Keywords: Ventricular Tachycardia; arrhythmia; dogs